A theology of mission : an analysis of the theology of mission of the Catholic Diocese of Darwin in its ministry to Aboriginal people during the episcopacy of John O'Loughlin MSC (1949-85) - Hearn, Peter, 1948- (Kensington, N.S.W. : Nelen Yubu Missiological Unit, 2003)
Study about missionary work on mission stations outside of Darwin; grounded in documents and anecdotal evidence; seeks to explore and define the concept of 'theology of mission'; methodology elicits different models of mission.
Bibliography.
Keywords: Catholic Church -- Missions -- Northern Territory; Aboriginal Australians -- Missions -- Northern Territory; Aboriginal Australians -- Religion; Religions - Christianity - Catholic Church; Religions - Christianity - Missions; Northern Territory (NT); Darwin (NT Top End SD52-04); Wadeye / Port Keats (Daly River NT Top End SD52-11); Daly River (NT Top End SD52-08); Ltyentye Apurte / Santa Teresa / Little Flower Mission (South Central NT SG53-02)